Co-Delivery of Curcumin and Bioperine via PLGA Nanoparticles to Prevent Atherosclerotic Foam Cell Formation - Sindhu C. Pillai; Ankita Borah; Minh Nguyen Tuyet Le; Hiroaki Kawano; Kouichi Hasegawa; D. Sakthi Kumar (MDPI AG, 2021)
Cholesterol-rich arterial plaques characterize atherosclerosis, a significant cause of heart disease. Nutraceuticals have received attention over the years, demonstrating potential benefits towards treating and preventing cardiovascular diseases (CVD), including atherosclerosis. Curcumin, a potent polyphenol present in Curcuma longa, has shown remarkable anti-atherosclerotic activity via anti-inflammatory and anti-oxidative properties. The bioavailability and low water solubility of curcumin limit its clinical translational purposes. These issues can be circumvented effectively by nano-drug delivery systems that can target atherosclerotic plaque sites. In this work, we chose to use curcumin and a natural bioenhancer called Bioperine (derived from Piper nigrum) inside a polymeric nano-drug delivery system for targeting atherosclerotic plaque sites. We selected two different ratios of curcumin:Bioperine to study its comparative effect on the inhibition of oxidized low-density lipoprotein (Ox-LDL)-induced foam cell formation. Our studies demonstrated that Cur-Bio PLGA NPs (both ratios) maintained the cell viability in THP-1 monocyte-derived macrophages above 80% at all periods. The 1:0.2:10 ratio of Cur-Bio PLGA NPs at a concentration of 250 μg/mL illustrated an enhanced reduction in the relative cholesterol content in the THP-1-derived foam cells compared to the 1:1:10 ratio. Confocal microscopy analysis also revealed a reduction in macrophage-mediated foam cell formation when administered with both the ratios of Cur-Bio PLGA NPs. Relative fold change in the mRNA expression of the genes involved in the inflammatory pathways in the atherosclerotic process downregulated NF-κB, CCL2/MCP-1, CD-36, and STAT-3 activity while upregulating the SCAR-B1 expression when treated with the Cur-Bio PLGA NPs. This study thus highlights the importance of natural-based compounds towards the therapeutic intervention against atherosclerotic activity when administered as preventive medicine.